Clinical Features of Focal Nodular Hyperplasia of the Liver in Children. Issue 6 (June 2016) - Ji, Yi; Chen, Siyuan; Xiang, Bo; Wen, Tianfu; Yang, Jiaying; Zhong, Lin; Li, Fuyu; Li, Li
ABSTRACT: Background: Focal nodular hyperplasia (FNH) is a benign hepatic lesion that is rare in children. The aim of the present study was to review the clinical features of children with FNH and our institution's experience in the management of this rare disease. Methods: A review of the medical records of children diagnosed as having FNH between 1999 and 2013 at West China Hospital of Sichuan University was undertaken. Results: Seventy-nine patients with FNH were identified: 68 patients without a history of malignancy and 11 patients with a history of malignancy. Thirty-seven (46.8%) patients were symptomatic at presentation. Patients with a history of malignancy had smaller FNH lesions and were less likely to have a central scar in FNH than do patients without a history of malignancy. Forty-seven patients underwent liver resection because of concern for malignancy, symptoms, and/or large lesions. Three patients were treated by embolization because of compression of the adjacent organs. There was no operative death or severe postoperative complications. Fourteen patients underwent liver biopsy to rule out malignant masses. The remaining 15 patients were managed expectantly with imaging surveillance. On follow-up, 2 patients for whom observation was initially recommended eventually required resection because of a mass effect. Conclusions: The clinical features of pediatric FNH are variable and can be nonspecific. Our data emphasize the therapeutic approach that active management is indicated in symptomatic or progressive FNH and in children with diagnostic difficulties, whereas observation management is recommended in asymptomatic children with a definitive diagnosis.